Acoustic Heating Produced in the Thermoviscous Flow of a Shear-Thinning Fluid - PERELOMOVA, Anna (Archives of Acoustics, 2011)
This study is devoted to the instantaneous acoustic heating of a shear-thinningfluid. Apparent viscosity of a shear-thinning fluid depends on the shear rate. Thatfeature distinguishes it from a viscous Newtonian fluid. The special linear combi-nation of conservation equations in the differential form makes it possible to derivedynamic equations governing both the sound and non-wave entropy mode inducedin the field of sound. These equations are valid in a weakly nonlinear flow of a shear-thinning fluid over an unbounded volume. They both are instantaneous, and do notrequire a periodic sound. An example of a sound waveform with a piecewise constantshear rate is considered as a source of acoustic heating.